Pengaruh Customer Experience dan Service Quality Terhadap Word of Mouth pada Hotel Bobobox dengan Customer Satisfaction sebagai Variabel Intervening - Firnanda Dwi Syahputra; Kussudyarsana Kussudyarsana (ITB AAS INDONESIA, 2024)
The purpose of this research is to determine whether customer experience and service quality can affect word of mouth mediated by customer satisfaction at Bobobox hotel. The method used in this research is quantitative research with the sampling technique used, namely non probability sampling, with purposive sampling method. The results in this research indicate that customer experience has no effect on word of mouth, but service quality affects word of mouth, customer experience affects customer satisfaction, service quality affects customer satisfaction, customer satisfaction affects word of mouth, customer satisfaction can mediate the relationship between customer experience and word of mouth, customer satisfaction can mediate the relationship between service quality and word of mouth. Keywords: Customer Experience, Service Quality, Word of Mouth, Customer Satisfaction